1997
DOI: 10.1046/j.1365-2125.1997.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin depresses hepatic cytochrome P450‐mediated drug metabolism in women

Abstract: Aims In men, the inflammatory response to intravenous endotoxin depresses apparent oral clearances of antipyrine, hexobarbitone, and theophylline. The aim of this study was to investigate whether there might be gender differences in the regulation of hepatic cytochromes P450. Methods Experiments were carried out in seven healthy women volunteers (ages 19-51, median 22 years). Each woman received a cocktail of the three drugs on two occassions, once after a saline injection and again after endotoxin. Results En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 9 publications
3
35
0
Order By: Relevance
“…This effect evolved over a 24 hour period and its intensity correlated with the intensity of the inflammatory response, although there was no statistically significant correlation between the observed effects and levels of any of the cytokines. A later study by the same investigators confirmed a similar effect in vivo in female volunteers (Shedlofsky et al, 1997). However, an inverse correlation has been reported between plasma IL-6 levels and cytochrome P450-dependent drug clearance of erythromycin (measured by breath test) by CYP3A4 in patients with advanced cancer (Rivory et al, 2002) and of caffeine and mephenytoin by CYP1A2 and CYP2C19, respectively, in patients with congestive heart failure (Frye et al, 2002).…”
Section: Clinical Evidence Suggestive Of Phenoconversion Of Dmes In Imentioning
confidence: 77%
See 1 more Smart Citation
“…This effect evolved over a 24 hour period and its intensity correlated with the intensity of the inflammatory response, although there was no statistically significant correlation between the observed effects and levels of any of the cytokines. A later study by the same investigators confirmed a similar effect in vivo in female volunteers (Shedlofsky et al, 1997). However, an inverse correlation has been reported between plasma IL-6 levels and cytochrome P450-dependent drug clearance of erythromycin (measured by breath test) by CYP3A4 in patients with advanced cancer (Rivory et al, 2002) and of caffeine and mephenytoin by CYP1A2 and CYP2C19, respectively, in patients with congestive heart failure (Frye et al, 2002).…”
Section: Clinical Evidence Suggestive Of Phenoconversion Of Dmes In Imentioning
confidence: 77%
“…IL-1, IL-6, and TNF-a are believed to be the principal proinflammatory cytokines that induce changes in liver protein expression; typically, they downregulate their expression. The precise mechanisms are not fully understood but these cytokines bind to their corresponding receptors on the cell surface in target organs and activate intracellular signaling systems that regulate gene transcription and biosynthesis of a whole range of enzymes and transporters, including those involved in drug metabolism and disposition (Shedlofsky et al, 1994(Shedlofsky et al, , 1997Morgan, 1997;Morgan et al, 1998;Renton, 2004Renton, , 2005Aitken et al, 2006;Le Vee et al, 2008, 2009Fardel and Le Vée, 2009). …”
Section: Downloaded Frommentioning
confidence: 99%
“…This defense mechanism and the release of these cytokines usually result in the down-regulation of many isoforms of cytochrome P450 (P450) (Ghezzi et al, 1986;Shedlofsky et al, 1987Shedlofsky et al, , 1997Bertini et al, 1988;Morgan 1989;Wright and Morgan 1990). This is important because of the major roles of the P450 systems in the metabolism of drugs used in the treatment of inflammatory conditions, as well as steroids, lipid-soluble vitamins, prostaglandins, and leukotrienes.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-␣, one of the cytokines prominent in the inflammatory response, is known to be released during many types of infections and inflammatory diseases (Shedlofsky et al, 1997). In the current study, we used this cytokine to define the effects of its presence on the regulation of CYP4F11, an isoform of the 4F family whose substrate profile includes not only endogenous compounds but also xenobiotics, specifically pharmaceuticals (Kalsotra et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation has been observed clinically to reduce P450-related hepatic drug metabolism (Renton et al, 1980;Sonne et al, 1985). In human and animal experimental systems, we and others have demonstrated a significant decrease in hepatic P450 activity following induction of the acute phase response (APR) by the administration of bacterial endotoxin (LPS) (Shedlofsky et al, 1994(Shedlofsky et al, , 1997Sewer et al, 1996;Roe et al, 1998;Warren et al, 1999Warren et al, , 2001. Elevated levels of cytokines [e.g., tumor necrosis factor-alpha (TNF␣), interleukin-6 (IL-6), and interleukin-1␤ (IL-1␤)] have been implicated as the primary mediators of the APR and the accompanying decline in hepatic P450 expression (Heinrich et al, 1990;Schindler et al, 1990;van Deventer et al, 1990;Parmentier et al, 1993Parmentier et al, , 1997Warren et al, 1999Warren et al, , 2001.…”
mentioning
confidence: 99%